Untilization Of Tiktok Digital Content As A Promotional Media Of Ms. Glow In Increasing Buying Interest In Medan City - auladari, tika; Simanjorang, Feronica (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2023)
This researcher has a background related to the phenomenon of using Tiktok digital content which is a new technology but is very quickly popular and is used as a promotional medium by business people. Through video shows and music displays, Tiktok facilitates information and can be transmitted and can explain stimulation to those who see it. The purpose of this study is to find out what factors influence the effectiveness of digital content in increasing buying interest during the covid-19 pandemic and to analyze the effectiveness of Tiktok digital content as a promotional medium in increasing buying interest during the covid-19 pandemic . In this study, the researcher used a qualitative method of descriptive research. Data collection techniques through interviews, observations, and documentation to MS. Glow business actors who promote through Tiktok digital content. The results of the research conducted indicate that business actors make use of Tiktok's digital content to be an effective promotional media because Tiktok has many users, is easy to use, is popular among young children.